Distribution of Some Liver Enzymes and Trace Elements ?in Serum of Thi-Qar Leukemia Patients - Abed, Nabeel; Maktoof , Afrah; Nuhair, Rsha (University of Thi-Qar Journal, 2022)
In the present study, the concentrations of ALT,AST,ALP total protein , urea and creatinine and some trace elements Cooper (Cu),Iron (Fe) and Zinc (Zn) in the serum of 40 adult patients with diagnosed of leukemia (after treatment) were studied. Samples were collected from oncology center/AL-Habboubi Teaching Hospital in Thi-Qar province, Serum levels of liver enzyme and trace elements were compared with(25) healthy group samples. It was found that a significant increase (P<0.05) in liver enzyme ALT, AST, ALP concentrations in blood serum of control and patients with leukemia . Also there is significant increase in urea serum level in patients at (p<0.05) and increase in creatinine but non significant . As regards the results of trace elements Serum levels of Cu and Fe elements were significantly higher in with leukemia patients than in the controls (p? 0.05). Also the level of Zinc was higher but statistically not significant (p>0.05).